An evidence-based review of neuronal cholesterol role in dementia and statins as a pharmacotherapy in reducing risk of dementia. (2nd December 2021) - Dutta, Siddhartha; Rahman, Sayeeda; Ahmad, Rahnuma; Kumar, Tarun; Dutta, Gitashree; Banerjee, Sudeshna; Abubakar, Abdullahi Rabiu; Rowaiye, Adekunle Babajide; Dhingra, Sameer; Ravichandiran, Velayutham; Kumar, Santosh; Sharma, Paras; et al.
ABSTRACT: Introduction: Dementia is a progressive neurodegenerative disorder impairing memory and cognition. Alzheimer's Disease, followed by vascular dementia – the most typical form. Risk factors for vascular dementia include diabetes, cardiovascular disease, hyperlipidemia. Lipids' levels are significantly associated with vascular changes in the brain. Areas Covered: The present article reviews the cholesterol metabolism in the brain, which includes: the synthesis, transport, storage, and elimination process. Additionally, it reviews the role of cholesterol in the pathogenesis of dementia and statin as a therapeutic intervention in dementia. In addition to the above, it further reviews evidence in support of as well as against statin therapy in dementia, recent updates of statin pharmacology, and demerits of use of statin pharmacotherapy. Expert Opinion: Amyloid-β peptides and intraneuronal neurofibrillary tangles are markers of Alzheimer's disease. Evidence shows cholesterol modulates the functioning of enzymes associated with Amyloid-β peptide processing and synthesis. Lowering cholesterol using statin may help prevent or delay the progression of dementia. This paper reviews the role of statin in dementia and recommends extensive future studies, including genetic research, to obtain a precise medication approach for patients with dementia.